Bilateral and unilateral asymmetries of strength and flexibility in young elite sailors: Windsurfing, Optimist and Laser classes - Caraballo, I.; González-Montesinos, J. L.; Alias, A. (symmetry, 2020)
In sport sailing, performance is related to the sailor`s ability to maintain the stability of the boat, and the boat class determines the variables involved in such ability. In monohull-type vessels, such as the Optimist and Laser classes, the flexibility of the hip joint is a key performance factor. In the Windsurfing class, performance is determined by the strength of the flexors of the fingers and elbows. The performance of the sailor may be a ected by asymmetries in the strength and flexibility of the muscles and joints involved in technical actions. The objective of this study was to evaluate asymmetries in strength and flexibility in young sailors. Thirty-three young sailors (ten girls) from the Windsurfing, Optimist and Laser classes were assessed for manual strength and flexibility, by dynamometry and straight leg lift tests, respectively. The symmetry index and the functional asymmetry of compression force were calculated. The results showed no di erences between sailors according to gender. The sailors of the Laser class obtained the highest levels of manual strength, whereas those of the Windsurfing class showed the highest flexibility levels. The girls` group andWindsurfing class had the highest percentage of sailors with strength asymmetry, whereas, the sailors of the Optimist class presented a greater percentage of asymmetry in flexibility. There were no di erences in upper limb strength and lower limb flexibility between the dominant and non-dominant sides.